1 Del. Rev. Stat. 716 (1893) - (:unkn) unknown (My University, 1893)
Ch. 548: Prohibited the concealed carrying of deadly weapons or selling deadly weapons other than an ordinary pocket knife, and prohibited discharging any firearm in any public road. Punishable by fine of $25-100 or by imprisonment for 10-30 days.
Keywords: CARRY - CONCEALED; DISCHARGE; TRANSFER